The Effect of Gender and Academic Levels Differences on Disaster Preparedness Knowledge of Pre-Service Teachers - Rima Meilita Sari; Ridhwan Ridhwan (Department of Geography Education, University of Jember, 2022)
The earthquake and tsunami experienced in Aceh created the importance of disaster preparedness. Efforts to improve disaster literacy, including knowledge of its effects, should be conducted. The aims of this study are 1) knowing the level of student’s disaster preparedness knowledge, 2) obtaining gender differences in disaster preparedness knowledge, 3) knowing the difference in academic level on disaster preparedness knowledge, 4) knowing the effect of interaction between gender and academic level on disaster preparedness knowledge. This research involved Geography pre-service teachers on STKIP Al-Washliyah. The results were quantitative data obtained from a disaster preparedness knowledge test, and data collection used multiple-choice tests. A knowledge test instrument was created and validated for data validity and reliability using a wondershare quiz generator. Data were analyzed using an index to decide the extent of knowledge on disaster preparedness. The ANCOVA approach was evaluated to examine the relationship between gender and educational degree. The results indicate that 1) the score for knowledge of disaster preparedness is 49.11, which indicates that knowledge is still in the low category, 2) there is a difference in knowledge of disaster preparedness between male and female pre-service geography teachers with a significant value of 0.004 (<0.05), 3) there is a difference in knowledge of pre-service geography teacher with different academic levels and significance value of 0.000 (<0.05), 4) when viewed from the interaction between gender and academic level, no significant relationship was found on knowledge of disaster preparedness with a score of 0.185 (p> 0.05). According to the findings, it is crucial to increase disaster preparedness knowledge in basic and advanced courses of geography education study programs. Therefore, pre-service geography teachers have good knowledge and skills in disaster preparedness. One of the steps to increase knowledge is providing teaching materials and disaster simulation programs. Keywords : Disaster preparedness knowledge; Pre-service teacher; Gender; Academic levels Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License